UPAYA MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK MELALUI METODE DISKUSI MATA PELAJARAN PPKN DI SMPN SATAP BONELOHE NO. 36 KEPULAUAN SELAYAR - Nur Amilah Mahpufah; Muh. Sudirman; Andi Aco Agus (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2024)
Efforts to Increase Students' Learning Motivation Through the Civics Subject Discussion Method at SMPN Satap Bonelohe No. 36 Selayar Islands. Thesis of the Department of Civics and Legal Sciences, Faculty of Social and Legal Sciences, Makassar State University, supervised by Muh. Sudirman and Andi Aco Agus. This research aims to find out: (1) the application of the discussion method in learning can contribute to increasing students’ learning motivation. (2) the influence of the success of the discussion method as a strategy to increase students’ learning motivation. This type of research uses qualitative methods, data collection techniques through observation, interviews and documentation, data sources come from 7 informants, as well as data analysis through data reduction, presentation of data, drawing conclusions and verification. The results of this research show that: (1) The application of the discussion method in learning is an effective way to encourage interaction between teachers and students and between fellow students. Where the teacher divides groups, then the teacher first explains the material that will be discussed, studentsare divided into groups and groups 2 which allows students to espress their thoughts and arguments during the lesson, the use of appropriate learning methods is one of the factors for teacher success in learning. (2) The success of the discussion method can be said to have been successful which can be seen from supporting data such as pretest and posttest carried out on students to assess learning outcomes and the results of this data show an increase in student learning outcomes so this proves that the discussion method is able to increase student learning motivation.